Toxicity of Malathion on Metabolic Activities in the River Cauvery of Tilapia Fish Oreochromis mossambicus - Ravichelvan, R (International Journal of Pharmaceutical & Biological Archive, 2014)
Toxicity of Malathion on Metabolic Activities in the River Cauvery of Tilapia Fish Oreochromis mossambicus